BIMBINGAN DAN KONSELING PADA SISWA NAKAL: STUDI KASUS SMK SUDIRMAN 1 WONOGIRI - IKHSAN, ZAINURI (2011)
Guidance and Counseling is an aid service to learners either individually or in groups, to stand alone and develop optimally through various types of services and activities based on prevailing norms. In general, this study aims to describe the characteristics of Guidance and Counseling at the naughty students in vocational school of Sudirman 1 Wonogiri. While the specific objectives of this research is to 1) describe the characteristics of student delinquency, 2) describe the relationship of work between guidance counseling and student, 3) describe the characteristics of guidance and counseling activities. The the research used qualitative by ethnographic research design at SMK Sudirman 1 Wonogiri. Sources of research data are obtained from informants, events, and documents. Informants in this study is the principal, vice principal of student, teacher of guidance counseling, homeroom, teachers and students. The event in this study is the process of guidance counseling at the naughty students. This research document is a document relating to the records, photographs related to guidance counseling, and other documents. The later collected data in the analysis of the data collection through data collection, data reduction, display and conclusion. The results can be presented below 1) Guidance and Counseling can overcome and even in these schools play an important role in almost every field ranging from prevention, problem solving to student delinquency up to provide better solutions for the future, especially for students. 2) Guidance and Counseling to students can create a harmonious relationship with students so it creates an atmosphere of nurturing (giving a sense of security) in developing a pattern, providing stimulation and encouragement, and to provide the widest opportunity to learners to progress in all areas. 3) Guidance and Counseling activities not only deal with violations of the discipline problems but also Guidance Counseling services in high school is the most fertile setting for the counselor because the counselor can contribute a maximum in facilitating the students who need guidance actualize their potency optimally.